2012
DOI: 10.1007/s10096-012-1764-x
|View full text |Cite
|
Sign up to set email alerts
|

An abbreviated MLVA identifies Escherichia coli ST131 as the major extended-spectrum β-lactamase-producing lineage in the Copenhagen area

Abstract: Rapid bacterial typing is a valuable and necessary tool in the prevention and detection of outbreaks. The purpose of this study was to adapt a multilocus variable number of tandem repeats analysis (MLVA) for analysis on a benchtop capillary electrophoresis instrument and compare the modified assay with multilocus sequence typing (MLST) for typing cefpodoxime-resistant Escherichia coli (E. coli). Further, we identified the causative resistance mechanisms and epidemiological type of infection for isolates produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…A similar fraction of ST131 among ESBL isolates was found in several international studies (24)(25)(26) and in a recent Danish study that, in contrast to our study, provided only limited characterization of the isolates (27).…”
Section: Discussionsupporting
confidence: 90%
“…A similar fraction of ST131 among ESBL isolates was found in several international studies (24)(25)(26) and in a recent Danish study that, in contrast to our study, provided only limited characterization of the isolates (27).…”
Section: Discussionsupporting
confidence: 90%
“…Pheno-and genotypic characterizations were performed by using the MAST-test, PCR, and DNA sequence analysis according to methods used at the clinical laboratory of Department of Clinical Microbiology, Hvidovre Hospital, Denmark (HVH) or at Statens Serum Institut (SSI) as previously described (15). Sequence type verification was performed via full multilocus sequence typing (MLST, using the Achtmann scheme [http://mlst.warwick.ac.uk/mlst/dbs/Ecoli]) by SSI, who also found that the isolate harbored the virulence factors kpsM II and iutA (15)(16)(17).…”
Section: Strainmentioning
confidence: 99%
“…An abbreviated version of MLVA for the detection of E. coli ST131 that uses a benchtop capillary electrophoresis instrument was developed by Nielsen et al (167). The exclusion of two loci affected the discriminatory power of the abbreviated MLVA, making it less discriminatory than the original assay.…”
Section: Multilocus Variable-number Tandem-repeat Analysismentioning
confidence: 99%